Mengapa masyarakat sektor informal belum memiliki asuransi BPJS kesehatan: persepsi dari pengusaha online? - Firman Firman; Helfi Agustin (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Why don't online shop workers enroll in BPJS health insurance? a case study from the City of YogyakartaPurposeThis study aimed to explore why an informal sector group has not decided to become a part of BPJS health by identifying knowledge or health insurance literacy.MethodThis research was a qualitative study with a phenomenology approach. Determination of informants was used by snowball sampling technique. Data collection was conducted with in-depth interviews with 15 people from an online entrepreneurs group who live around the city of Yogyakarta. Data were identified with inductive thematic analysis related to health insurance literacy to determine any relationship pattern of research variables.ResultsThe majority of informants have knowledge health insurance as a health care program used to seek treatment when sick. Specifically, informants have difficulties in understanding and explaining the basic terms about BPJS health insurance such as membership type, premium, benefits package, services procedure, the way of registration. The main determinant is caused by personal factors of informants themselves who are not seeking information about BPJS health because busy with works, still young, unmarried, and get ill rarely. Another factor is informants more often rely on getting insurance information from friends or family, while information from the Government and BPJS organization itself is very rare.ConclusionLow health insurance literacy is the main cause why informants decide not to be participants in BPJS health insurance. So it’s necessary to educate people about the BPJS health insurance both from the government, BPJS organization, and especially health providers in health facilities.